Cu3 (HHTP) 2-loaded graphene-based nano composite wave-absorbing material as well as preparation method and application of Cu3 (HHTP) 2-loaded graphene-based nano composite wave-absorbing material

By introducing Cu3 (HHTP)2 load into graphene-based nanocomposite absorbing materials and using redox composite technology to build an interface charge transfer channel, the problems of impedance mismatch and narrow frequency range of existing carbon-based absorbing materials in the field of electromagnetic wave absorption are solved, and efficient electromagnetic wave absorption performance and the lightweight and low-cost characteristics of the material are achieved.

CN119505593APending Publication Date: 2025-02-25NANJING UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411561462.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing carbon-based absorbing materials face limited attenuation capabilities and narrow electromagnetic response frequency ranges caused by impedance mismatch in the field of electromagnetic wave absorption, and cannot effectively shield electromagnetic wave pollution.

Method used

Using Cu3(HHTP)2-loaded graphene-based nanocomposite wave absorbing material, the atomic interface charge transfer channel between the conductive complex and reduced graphene oxide is constructed through redox refinement technology, enhancing the built-in electric field at the interface, thereby improving the electromagnetic wave absorption performance.

Benefits of technology

It achieves efficient electromagnetic wave absorption performance, effective absorption bandwidth up to 6.36 GHz, reflection loss up to -75.43 dB, and light material quality and low cost, which is suitable for electrochemical devices and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505593A_ABST
    Figure CN119505593A_ABST
Patent Text Reader

Abstract

The invention discloses a Cu3 (HHTP) 2 loaded graphene-based nano-composite wave-absorbing coating and a preparation method and application of the Cu3 (HHTP) 2 loaded graphene-based nano-composite wave-absorbing coating. The wave-absorbing agent is prepared through a one-pot method, is excellent in wave-absorbing performance and can be used in the field of electromagnetic wave absorbing and shielding. According to the nano composite wave-absorbing coating disclosed by the invention, when the matching thickness is 2.0 mm, the effective absorption bandwidth is 6.36 GHz, and when the matching thickness is 4.8 mm, the minimum reflection loss is-75.43 dB. The preparation is simple, the cost is low, the application is simple and convenient, and the application prospect is relatively wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nanomaterials, and in particular to a Cu3(HHTP)2-loaded graphene-based nanocomposite wave-absorbing material. Background Art

[0002] The rapid development of emerging equipment such as electronic communications and intelligent detection has brought high-quality production and life to people in modern society, but it often causes a lot of harmful electromagnetic radiation or pollution. These radiations will inevitably interfere with the normal operation of precision electronic components or the accurate response of information detection, and even threaten human health. Therefore, it is urgent to prevent electromagnetic wave pollution. It is of great significance to further develop materials that can effectively weaken or shield electromagnetic waves.

[0003] At present, the most common carbon-based absorbing materials (graphene, carbon nanotubes, etc.) have practical advantages such as light weight, high conductivity, and strong stability, but they still face limited attenuation capacity and narrow electromagnetic response frequency range caused by impedance mismatch (S. Feng, F. Zhai, H. Su, D. Sridhar, H. Algadi, BB Xu, RAPashameah, E. Alzahrani, HM Abo-Dief, Y. Ma, T. Li, Z. Guo, Materials Today Physics 2023, 30 , 100950.). This reflects the limitations of a series of carbon-based absorbing materials in the field of electromagnetic wave absorption.

[0004] Conductive complexes have attracted widespread attention due to their porosity, high specific surface area, and low density, and are expected to become potential lightweight porous absorbers. Another irreplaceable advantage of them as absorbers is that their structure is clear and adjustable. Compared with other absorbers, the magnetic loss, dielectric loss, and impedance matching of conductive complexes can be tuned by coordination groups and metal ions, which is of great significance for achieving fine-tuning of the absorbent properties of materials (C. Chen, Z. Shan, S. Tao, A. Xie, H. Yang, J. Su, S. Horke, S.Kitagawa, G. Zhang, Advanced Functional Materials2023, 2305082; CA Peeples,D. Kober, F.-J. Schmitt, P. Tholen, K. Siemensmeyer, Q. Halldorson, B. Çoşut,A. Gurlo, AO Yazaydin, G. Hanna, G. Yücesan, Advanced Functional Materials 2021, 31 , 2007294.). On this basis, in order to further improve the performance, combining conductive complexes with lightweight carbon matrix materials through interface enhancement is an economical and efficient strategy. Due to the sudden change of the microstructure (lattice or electron) between the materials in the interface area, the composite material will have new and unique properties (L. Liang, W. Gu, Y. Wu, B. Zhang, G. Wang, Y. Yang, G. Ji, Advanced Materials 2022, 34 , 2106195.). During the modulation process of the composite element, some interfaces / defects will change, and the resulting polarization is highly adjustable. Therefore, the combined optimization and structural design of heterogeneous interfaces will bring about the characteristics of thin thickness, wide absorption bandwidth, and strong absorption capacity that are difficult to achieve with a single element (K. Cao, W. Ye, Y. Zhang, Z. Chen, R.Zhao, W. Xue, Chemical Engineering Journal 2024, 489 , 151384.).

[0005] At present, the research on composites mainly focuses on the composite strategy of pyrolysis derivatives. Conductive complexes composed of magnetic metals are a good precursor, which can be converted into magnetic metal / carbon-based composites by pyrolysis at different temperatures (H.Yu, X. Kou, X. Zuo, D. Xi, H. Guan, P. Yin, L. Xu, Y. Zhao, Journal of Materials Science&Technology 2024, 176 , 176.). Using Co-MOF three-dimensional microsphere composites as precursors, Che Renchao's group prepared Co / CoO / rGO, which has an excellent minimum reflection loss (RLmin) of –50.1 dB and an effective absorption bandwidth (EAB) of 6.56 GHz (Q. Li, J. Tan, Z. Wu, L. Wang, W. You, L. Wu, R. Che, Carbon 2023, 201, 150.). However, the widely used pyrolysis strategy will cause the original microstructure to collapse, making it still unclear to explore the absorption mechanism from the microscopic topological structure and phase composition. Similarly, CN201910614206.6 proposed a GO / Cu-HHTP composite material, which was prepared by a conventional pyrolysis strategy. No redox reaction occurred at the contact interface, and no precise atomic interface charge transfer channel was constructed between the conductive complex and the reduced graphene oxide in the form of a chemical bond. Summary of the invention

[0006] In order to make up for the defects of the prior art, the present invention provides a Cu3(HHTP)2-loaded graphene-based nanocomposite absorbing material and its preparation method and application. The technical solution of the present invention is described as follows: A Cu3(HHTP)2-loaded graphene-based nanocomposite wave absorbing material and a preparation method thereof, comprising the following steps: S1, adding graphite oxide powder to water and dispersing it evenly to obtain a graphite oxide powder dispersion; S2, adding 2,3,6,7,10,11-hexahydroxytriphenyl and cuprous chloride to the graphite oxide powder dispersion prepared in S1 in sequence to obtain a mixed solution; S3, after being uniformly dispersed, N,N-dimethylformamide is added to the mixed solution obtained in S2 for oxidation reaction to obtain Cu3(HHTP)2-rGO.

[0007] Preferably, the concentration of the graphite oxide powder dispersion in S1 is 0.8-1.2 g / L.

[0008] Preferably, the mass ratio of graphite oxide powder to 2,3,6,7,10,11-hexahydroxytriphenyl in the mixed solution obtained in S2 is 1:2-1:6; the mass ratio of 2,3,6,7,10,11-hexahydroxytriphenyl to cuprous chloride is 0.8:1-2:1.

[0009] Preferably, the volume ratio of N,N-dimethylformamide to the mixed solution in S3 is 1:5-1:11.

[0010] Preferably, the temperature of the oxidation reaction in S3 is 60-110° C., and the reaction time is 24-48 h.

[0011] Preferably, the preparation method adopts the following steps: S1, adding graphite oxide powder to water and performing ultrasonic dispersion treatment to prepare a 1 g / L graphite oxide powder dispersion; S2, adding 2,3,6,7,10,11-hexahydroxytribenzene to the graphite oxide powder dispersion obtained in S1, and adding cuprous chloride to obtain a mixed solution after uniform dispersion; the mass ratio of the added amount of 2,3,6,7,10,11-hexahydroxytribenzene to the added amount of graphite oxide powder in S1 is 2.6:1-2.7:1; the mass ratio of the added amount of 2,3,6,7,10,11-hexahydroxytribenzene to the added amount of cuprous chloride is 1.8:1-1.85:1; S3, after the mixed solution obtained in S2 is evenly dispersed, N,N-dimethylformamide solution is added to carry out oxidation reaction; the reaction temperature of the oxidation reaction is 95°C and the reaction time is 24h; after the reaction is completed, Cu3(HHTP)2-rGO is obtained; the volume ratio of the amount of the N,N-dimethylformamide solution added to the volume of the graphite oxide powder dispersion obtained in S1 is 1:8.

[0012] The invention provides a Cu3(HHTP)2-loaded graphene-based nanocomposite absorbing material. The Cu3(HHTP)2-loaded graphene-based nanocomposite absorbing material is prepared by mixing a monovalent copper compound solution with graphite oxide powder and 2,3,6,7,10,11-hexahydroxytriphenyl to obtain an oxidizing solution, and then subjecting the oxidizing solution to an oxidation reaction with N,N-dimethylformamide.

[0013] Preferably, the monovalent copper compound solution is selected from cuprous chloride solution, cuprous iodide solution, cuprous bromide solution, and cuprous cyanide solution.

[0014] The present invention provides an application of the Cu3(HHTP)2-loaded graphene-based nanocomposite absorbing material, and the absorbing material is applied to electromagnetic wave absorption and shielding.

[0015] Preferably, the Cu3(HHTP)2-loaded graphene-based nanocomposite absorbing material is mixed with polyvinyl butyral in a mass ratio of 1:4-1:6 and then dispersed in an ethanol solution, and the mixture is evenly mixed to obtain a Cu3(HHTP)2-rGO absorbing coating.

[0016] Preferably, the Cu3(HHTP)2-loaded graphene-based nanocomposite absorbing material needs to be ground to a particle size of 300-1000 mesh; the molecular weight of the polyvinyl butyral is 170,000-200,000; and the mass concentration of the polyvinyl butyral relative to the polyvinyl butyral-ethanol system is 0.3 wt%-0.6 wt%.

[0017] Beneficial Effects Compared with the prior art, the present invention utilizes a new composite mechanism to perform functional design on the composite material, and further adjusts the electromagnetic parameters of the composite material by changing the composite ratio and thickness, thereby improving the electromagnetic wave absorption performance. The present invention adopts a chemical design strategy for the first time to introduce the Cu3(HHTP)2-loaded graphene-based nanocomposite material (Cu3(HHTP)2-rGO) prepared by an in-situ redox one-pot method into the field of electromagnetic wave absorption. The Cu3(HHTP)2-rGO absorbing coating has excellent electromagnetic wave absorption performance. The present invention has the following advantages: (1) The preparation method of the present invention is simple to operate, safe and controllable, and has low energy consumption. The Cu3(HHTP)2-rGO obtained has a large and regular aspect ratio of the Cu3(HHTP)2 crystal rod on the surface, and the rGO sheet (reduced graphene oxide sheet) is thin and dispersed. The Cu3(HHTP)2-rGO is light in weight and has a blue-black overall macroscopic appearance.

[0018] (2) The Cu3(HHTP)2-rGO of the present invention has higher binding force and better conductivity. Its conductivity can reach 10 3 S / m is increased by 57% compared with the pure conductive complex. Therefore, Cu3(HHTP)2-rGO coating is also suitable for electrochemical devices and other fields as a surface coating.

[0019] (3) The advantage of the redox composite technology used in the present invention is that the interface charge transfer channel between the conductive complex and the reduced graphene oxide atoms is rationally constructed by utilizing the high-density dispersed metal sites of the conductive complex, thereby enhancing the built-in electric field of the interface and significantly improving the electromagnetic wave absorption performance.

[0020] (4) The present invention uses a chemical design strategy and an in-situ redox one-pot strategy to prepare a Cu3(HHTP)2-loaded graphene-based nanocomposite material, Cu3(HHTP)2-rGO, which has the characteristics of light weight, low cost and good wave absorption performance. It can be used as a wave absorbing coating. When the matching thickness is 2.0 mm, the effective absorption bandwidth is as high as 6.36 GHz. When the matching thickness is 4.8 mm, the reflection loss can reach -75.43 dB.

[0021] (5) The coating prepared by the present invention can be directly sprayed on the surface of the device to be processed using a spray gun, and can perform electromagnetic wave absorption and shielding treatment on the device to be processed in multiple scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the X-ray diffraction pattern of Cu3(HHTP)2-rGO-1 prepared in Example 1.

[0023] Figure 2This is a scanning electron microscope image of Cu3(HHTP)2-rGO-1 prepared in Example 1.

[0024] Figure 3 The conductivity diagrams of Cu3(HHTP)2 and Cu3(HHTP)2-rGO-1, Cu3(HHTP)2-rGO-2, and Cu3(HHTP)2-rGO-3 prepared in Examples 1 to 3.

[0025] Figure 4 This is a test diagram of the wave absorption performance of Cu3(HHTP)2-rGO-1 prepared in Example 1. Under the condition of matching thickness of 1.7 mm, the minimum reflection loss is -20.28 dB.

[0026] Figure 5 This is a test diagram of the wave absorption performance of Cu3(HHTP)2-rGO-2 prepared in Example 2. Under the condition of matching thickness of 4.8 mm, the minimum reflection loss is -75.44 dB.

[0027] Figure 6 This is a test diagram of the wave absorption performance of Cu3(HHTP)2-rGO-3 prepared in Example 3. Under the condition of matching thickness of 4.4 mm, the minimum reflection loss is -54.19 dB.

[0028] Figure 7 This is a schematic diagram of the actual A1-Cu3(HHTP)2-rGO-2 absorbing coating sprayed resin plate prepared in Example 4 (the left picture is before spraying, and the right picture is after spraying).

[0029] Figure 8 These are test graphs of the microwave absorption performance of the thin film layers of the resin plates sprayed with the microwave absorption coatings A1-Cu3(HHTP)2-rGO-2, A2-Cu3(HHTP)2-rGO-2 and A3-Cu3(HHTP)2-rGO-2 prepared in Examples 4 to 6. DETAILED DESCRIPTION

[0030] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.

[0031] Example 1 The preparation method of Cu3(HHTP)2-rGO-1 comprises the following steps: (1) preparing a graphite oxide powder aqueous solution, weighing 0.026 g of graphite oxide powder and adding it to 26 mL of deionized water, and ultrasonically crushing and dispersing it for 1 hour to obtain a 1 g / L graphite oxide powder aqueous solution; the specifications of the graphite oxide powder are: purity> 99%, flake diameter 0.5-5 μm, thickness 1-3 nm; (2) Preparation of Cu3(HHTP)2-rGO-1: 0.14 g HHTP was added to a beaker containing 26 mL of graphite oxide powder aqueous solution (1 g / L), and ultrasonically dispersed for 5 min. 0.077 g cuprous chloride was added to the above solution that was uniformly dispersed by ultrasonication. Ultrasonication was continued for another 5 min, and 5 mL of N,N-dimethylformamide solution was pipetted with a pipette and dropped into the above uniformly dispersed solution. (3) The reaction solution of step (2) was heated and stirred in an oil bath at 95°C for 24 hours. After cooling to room temperature, the black precipitate obtained by the reaction was separated by suction filtration. The black solid was washed alternately with deionized water and methanol three times each. The obtained black product was vacuum dried at 60°C for 12 hours. Finally, Cu3(HHTP)2-rGO-1 was obtained.

[0032] The Cu3(HHTP)2-rGO-1 prepared in Example 1 was subjected to X-ray diffraction measurement. The results are as follows Figure 1 As shown: Figure 1 This is the X-ray powder diffraction pattern of Cu3(HHTP)2-rGO in Example 1. From the figure, it can be seen that Cu3(HHTP)2-rGO has characteristic diffraction peaks belonging to Cu3(HHTP)2, which confirms that after the in-situ redox process, Cu3(HHTP)2 is generated on the surface of the reduced graphene oxide sheet obtained by the reduction of the copper source.

[0033] Example 2 The preparation method of Cu3(HHTP)2-rGO-2 comprises the following steps: (1) preparing a graphite oxide powder aqueous solution, weighing 0.04 g of graphite oxide powder, adding it to 40 mL of deionized water, and ultrasonically crushing and dispersing it for 1 hour to obtain a 1 g / L graphite oxide powder aqueous solution; (2) Preparation of Cu3(HHTP)2-rGO-2: 0.14 g HHTP was added to a beaker containing 40 mL of graphite oxide powder aqueous solution (1 g / L), and ultrasonically dispersed for 5 min. 0.077 g cuprous chloride was added to the ultrasonically dispersed solution. Ultrasonication was continued for another 5 min, and 5 mL of N,N-dimethylformamide solution was pipetted and dropped into the uniformly dispersed solution. (3) The reaction solution of step (2) was heated and stirred in an oil bath at 95°C for 24 hours. After cooling to room temperature, the black precipitate obtained by the reaction was separated by suction filtration. The black solid was washed alternately with deionized water and methanol three times each. The obtained black product was vacuum dried at 60°C for 12 hours. Finally, Cu3(HHTP)2-rGO-2 was obtained.

[0034] The Cu3(HHTP)2-rGO-2 prepared in Example 2 was measured by transmission electron microscopy. Figure 2 As shown: Figure 2 This is a scanning electron microscope image of Cu3(HHTP)2-rGO-2 in Example 2, showing the unique hexagonal structure of Cu3(HHTP)2 and the ultra-thin reduced graphene oxide sheets. The monovalent copper introduced into the system is first oxidized at the active sites (-COOH, -OH, =O, etc.) on the surface of graphene oxide and then anchored on the surface of the graphene sheet, and then coordinated with the deprotonated HHTP in the system to form a conductive complex Cu3(HHTP)2 with good crystallinity using the remaining copper source.

[0035] Example 3 The preparation method of Cu3(HHTP)2-rGO-3 comprises the following steps: (1) preparing a graphite oxide powder aqueous solution, weighing 0.053 g of graphite oxide powder, adding it to 53 mL of deionized water, and ultrasonically crushing and dispersing it for 1 hour to obtain a 1 g / L graphite oxide powder aqueous solution; (2) Preparation of Cu3(HHTP)2-rGO-3: 0.14 g HHTP was added to a beaker containing 53 mL of graphite oxide powder aqueous solution (1 g / L), and ultrasonically dispersed for 5 min. 0.077 g cuprous chloride was added to the above solution that was uniformly dispersed by ultrasonication. Ultrasonication was continued for another 5 min, and 5 mL of N,N-dimethylformamide solution was pipetted with a pipette and dropped into the above uniformly dispersed solution. (3) The reaction solution of step (2) was heated and stirred in an oil bath at 95°C for 24 hours. After cooling to room temperature, the black precipitate obtained by the reaction was separated by suction filtration. The black solid was washed alternately with deionized water and methanol three times each. The obtained black product was vacuum dried at 60°C for 12 hours. Finally, Cu3(HHTP)2-rGO-3 was obtained.

[0036] Figure 3The conductivity measurement diagram of Cu3(HHTP)2 and Cu3(HHTP)2-rGO-1, Cu3(HHTP)2-rGO-2, and Cu3(HHTP)2-rGO-3 obtained in Examples 1 to 3 is shown. The mass ratio of the sample to the paraffin in the test is 3:7. Among them, the sample Cu3(HHTP)2 to be tested is prepared by a classical method. The preparation scheme is as follows: copper acetate monohydrate (0.78 g) and HHTP (0.7 g) are added to 150 ml of deionized water, and finally 15 ml of N,N-dimethylformamide is added. The reaction mixture is ultrasonicated for 15 minutes and stirred at 80°C for 6 hours. The precipitated Cu3(HHTP)2 is filtered and washed with deionized water and methanol.

[0037] observe Figure 3 It can be seen that the electrical conductivities of Cu3(HHTP)2, Cu3(HHTP)2-rGO-1, Cu3(HHTP)2-rGO-2 and Cu3(HHTP)2-rGO-3 are 2.65 S / m, 90.0 S / m, 120.5 S / m and 153.8 S / m, respectively. It can be seen that the electrical conductivity of Cu3(HHTP)2 is significantly enhanced after being composited with graphene, and the electrical conductivity can be adjusted by changing the concentration of graphene.

[0038] Figures 4 to 6 This is a test graph of the wave absorption performance of Cu3(HHTP)2-rGO-1, Cu3(HHTP)2-rGO-2, and Cu3(HHTP)2-rGO-3 obtained in Examples 1 to 3. Figures 4 to 6 As can be seen in the figure: the minimum reflection losses corresponding to Cu3(HHTP)2-rGO-1, Cu3(HHTP)2-rGO-2, and Cu3(HHTP)2-rGO-3 are -20.28 dB (under the condition of matching thickness of 1.7 mm), -75.43 dB (under the condition of matching thickness of 4.8 mm), and -54.19 dB (under the condition of matching thickness of 4.4 mm), respectively, and the effective absorption bandwidths are 6.10 GHz, 6.36 GHz, and 4.72 GHz, respectively. The above results show that the absorption performance of Cu3(HHTP)2-rGO can be regulated by changing the amount of graphene oxide in the system and controlling the additional atomic-level charge transfer channel.

[0039] Example 4 Take 0.03 g of Cu3(HHTP)2-rGO-2 prepared in Example 4, grind it and add it to 30 g of ethanol solution containing 0.12 g of polyvinyl butyral, stir it thoroughly to obtain A1-Cu3(HHTP)2-rGO-2 absorbing coating.

[0040] Example 5 Take 0.03 g of Cu3(HHTP)2-rGO-2 prepared in Example 4, grind it and add it to 30 g of ethanol solution containing 0.15 g of polyvinyl butyral, stir it thoroughly to obtain A2-Cu3(HHTP)2-rGO-2 absorbing coating.

[0041] Example 6 Take 0.03 g of Cu3(HHTP)2-rGO-2 prepared in Example 4, grind it and add it to 30 g of ethanol solution containing 0.18 g of polyvinyl butyral, stir it thoroughly to obtain A3-Cu3(HHTP)2-rGO-2 absorbing coating.

[0042] By comparing and analyzing Examples 4 to 6, the coatings A1-Cu3(HHTP)2-rGO-2, A2-Cu3(HHTP)2-rGO-2 and A3-Cu3(HHTP)2-rGO-2 prepared from Cu3(HHTP)2-rGO-2 and polyvinyl butyral at a mass ratio of 1:4, 1:5 and 1:6 respectively. The minimum reflection loss of the finished product A2-Cu3(HHTP)2-rGO-2 after spraying is as low as -35.80 dB (e.g. Figure 8 As shown in Figure 2, as the sample matching thickness increases, Cu3(HHTP)2-rGO exhibits stronger reflection loss for lower frequency electromagnetic waves. Therefore, the frequency of minimum reflection loss and effective absorption bandwidth coverage can be adjusted by changing the sample matching thickness, thus achieving adjustable absorption performance of electromagnetic wave absorbing materials.

[0043] Example 7 The Cu3(HHTP)2-rGO-2 absorbing coating in Example 4 was sprayed onto the resin plate using a spray gun under an air compressor. The liquid and gas volumes were controlled appropriately to make the spray fine. After the first layer was slightly dry, multiple layers were sprayed to control the coating thickness. The volatile ethanol solution dried in about 5 minutes to form a homogeneous gray film. Its absorbing properties were measured.

[0044] Figure 7 This is a schematic diagram of the actual resin plate in Example 4 before spraying (left) and after spraying (right).

Claims

1. A Cu3(HHTP)2-loaded graphene-based nanocomposite absorbing material, characterized in that: The Cu3(HHTP)2-loaded graphene-based nanocomposite wave-absorbing material is prepared by mixing a monovalent copper compound solution with graphite oxide powder and 2,3,6,7,10,11-hexahydroxytriphenyl to obtain an oxidizing solution, and then subjecting the oxidizing solution to an oxidation reaction with N,N-dimethylformamide.

2. The preparation method according to claim 1, characterized in that: The monovalent copper compound solution is selected from cuprous chloride solution, cuprous iodide solution, cuprous bromide solution, and cuprous cyanide solution.

3. A method for preparing a Cu3(HHTP)2-loaded graphene-based nanocomposite absorbing material, characterized in that: The steps include: S1, adding graphite oxide powder to water and dispersing it evenly to obtain a graphite oxide powder dispersion; S2, adding 2,3,6,7,10,11-hexahydroxytriphenyl and cuprous chloride to the graphite oxide powder dispersion prepared in S1 in sequence to obtain a mixed solution; S3, after being uniformly dispersed, N,N-dimethylformamide is added to the mixed solution obtained in S2 for oxidation reaction to obtain Cu3(HHTP)2-rGO.

4. The preparation method according to claim 3, characterized in that: The concentration of graphite oxide powder dispersion in S1 is 0.8~1.2 g / L; and / or the mass ratio of graphite oxide powder to 2,3,6,7,10,11-hexahydroxytriphenyl in the mixed solution obtained from S2 is 1:2-1:6; the mass ratio of 2,3,6,7,10,11-hexahydroxytriphenyl to cuprous chloride is 0.8:1-2:1; And / or the volume ratio of N,N-dimethylformamide to the mixed liquid in S3 is 1:5~1:

11.

5. The preparation method according to claim 3, characterized in that: The temperature of the oxidation reaction in S3 is 60-110° C., and the reaction time is 24-48 hours.

6. The preparation method according to claim 3, characterized in that: The preparation method adopts the following steps: S1, adding graphite oxide powder to water and performing ultrasonic dispersion treatment to prepare a 1 g / L graphite oxide powder dispersion; S2, adding 2,3,6,7,10,11-hexahydroxytribenzene to the graphite oxide powder dispersion obtained in S1, and adding cuprous chloride to obtain a mixed solution after uniform dispersion; the mass ratio of the added amount of 2,3,6,7,10,11-hexahydroxytribenzene to the added amount of graphite oxide powder in S1 is 2.6:1-2.7:1; the mass ratio of the added amount of 2,3,6,7,10,11-hexahydroxytribenzene to the added amount of cuprous chloride is 1.8:1-1.85:1; S3, after the mixed solution obtained in S2 is evenly dispersed, N,N-dimethylformamide solution is added to carry out oxidation reaction; the reaction temperature of the oxidation reaction is 95°C and the reaction time is 24h; after the reaction is completed, Cu3(HHTP)2-rGO is obtained; the volume ratio of the amount of the N,N-dimethylformamide solution added to the volume of the graphite oxide powder dispersion obtained in S1 is 1:

8.

7. A Cu3(HHTP)2-loaded graphene-based nanocomposite absorbing material, characterized in that: The Cu3(HHTP)2-loaded graphene-based nanocomposite absorbing material is prepared according to the preparation method according to any one of claims 3 to 6.

8. An application of the Cu3(HHTP)2-loaded graphene-based nanocomposite absorbing material as claimed in claim 7, characterized in that: The Cu3(HHTP)2-loaded graphene-based nanocomposite absorbing material is used for electromagnetic wave absorption and shielding.

9. The use according to claim 8, characterized in that: The Cu3(HHTP)2-loaded graphene-based nanocomposite absorbing material is mixed with polyvinyl butyral in a mass ratio of 1:4-1:6 and then dispersed in an ethanol solution. After mixing evenly, a Cu3(HHTP)2-rGO absorbing coating is obtained.

10. The use according to claim 9, characterized in that: The Cu3(HHTP)2-loaded graphene-based nanocomposite absorbing material needs to be ground to a particle size of 300-1000 mesh; the molecular weight of the polyvinyl butyral is 170,000-200,000; and the mass concentration of the polyvinyl butyral relative to the polyvinyl butyral-ethanol system is 0.3 wt%-0.6 wt%.

Citation Information

Patent Citations

  • Heat-insulation wave-absorbing material and preparation method thereof

    CN110157316A